Vehicle Stop Detection Algorithm Based on Motion Analysis in Access Control System Application - Majidi, A.; Pourghassem, H.; Nejati, M. (2012 4th International Conference on Computational Intelligence and Communication Networks, 2012)
In This paper, a vehicle stop detection algorithm based on motion analysis in access control system application is proposed. In this algorithm, motion of vehicle in consecutive frames is analyzed and used to determination of frame in which vehicle has been stopped. Motion analysis is carried out based on thresholded difference image calculated for each two sequential frames of a video stream and a verification mask which shows the variations of important edges in these two frames. Then, a decision value is extracted from the refined difference image that determines the vehicle stop frame. In this algorithm, an adaptive thresholding approach based on decision value of previous frames is proposed that compensates the various illumination conditions in day and night. The proposed vehicle stop detection algorithm was evaluated on several videos captured in day and night. The obtained results show efficiency of the proposed algorithm in real and operational conditions.